2022
DOI: 10.56983/jlta.v2i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Students Learning Style by Using Neil Fleming’s Vark Model and Inventory

Abstract: This research deals language learning styles of the first-grade students of SMP Neheri 3 Bontomarannnu. The problem statement are : (1) Which language learning style is the most dominant used by the first grade students of SMP Negeri 3 Bontomarannu? (2) Do the students’ learning styles influence their English achievement? The objective of the research is to find out the most dominant language learning style used by the first-grade students of SMP Negeri 3 Bonromarannu. (2) To found the influence of studens lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…These results are in agreement with the findings conducted by (Niga & Janggo, 2022;Siddiquei & Khalid, 2022) which revealed that visual learning style was typically preferred among all the learning styles of students. These results are also consistent with the findings of (Jumrah, 2022;Rasdi & Rusli, 2023) which showed that the most common of the learning styles of students was visual learning. Similarly, (Dakay et al, 2023) also confirmed that based on the data, the learning style of the students' majority was visual students.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…These results are in agreement with the findings conducted by (Niga & Janggo, 2022;Siddiquei & Khalid, 2022) which revealed that visual learning style was typically preferred among all the learning styles of students. These results are also consistent with the findings of (Jumrah, 2022;Rasdi & Rusli, 2023) which showed that the most common of the learning styles of students was visual learning. Similarly, (Dakay et al, 2023) also confirmed that based on the data, the learning style of the students' majority was visual students.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…In this study, the instrument used was a questionnaire consisting of 20 questions. The instrument provided is an instrument adopted from (Jumrah, 2022) which deals with types of learning styles by VARK Neil Fleming. The questions given are in the form of questions to find out 4 types of student learning styles such as; visual, auditory, read/write, and kinesthetic.…”
Section: Instrumentmentioning
confidence: 99%